Body and surrealism: on the quiasm in César Moro’s The equestrian turtle and Luis Buñuel’s An andalusian dog - Cabrejo Cobián, José Carlos (2021)
This essay explores how the poetry book The Equestrian Turtle by César Moro, written between 1938 and 1939, and the short film An Andalusian Dog by Luis Buñuel, released in 1929, two emblematic works of the surrealist avant-garde, addressed the iconic representation of the body. On the one had, this phenomenonis analyzedfrom the perspective of the chiasm found in the work of the philosopher Maurice Merleau-Ponty; on the other, from generative (Algirdas Julien Greimas and Joseph Courtés) and tensive (Jacques Fontanille and Claude Zilberberg) semiotics. The conclusion reached is that these works confirm that the surrealist discourse in poetry and cinema takes an awareness of chiasm through iconicity, by focusing the body and the world as a single entity, in an integral and unitary way.